Clinical and biological characteristics of myeloma patients influence response to elotuzumab combination therapy - Danhof, Sophia; Strifler, Susanne; Hose, Dorothea; Kortuem, Martin; Bittrich, Max; Hefner, Jochen; Einsele, Hermann; Knop, Stefan; Schreder, Martin (Journal of Cancer Research and Clinical Oncology, 2019)
Based on ELOQUENT-2, combination therapy with the monoclonal antibody elotuzumab was approved for relapsed/refractory multiple myeloma in the US and Europe. However, outside clinical trials, the optimal integration of elotuzumab into the sequence of treatment lines remains to be determined. Therefore, we analyzed safety and efficacy of elotuzumab/immunomodulatory drug combinations in a real-life cohort of 33 patients from our institution. The most frequent grade 3/4 adverse event was lymphopenia which did not increase the incidence of viral reactivations. After a median of four prior treatment lines, an overall response rate of 60% and a median progression-free survival (PFS) of 8 months were observed. The presence of cytogenetic high-risk status had no impact on PFS while low disease burden and high numbers of natural killer (NK)-cells at treatment initiation were associated with longer PFS. We observed an extramedullary relapse in three patients, associated with reduced expression of the elotuzumab target antigen SLAMF7 on extramedullary myeloma cells in one patient. Thus, biomarkers like disease burden, NK-cell count and SLAMF7 expression on myeloma cells may help to define myeloma patients with high likelihood to respond to elotuzumab treatment. Prospective trials investigating these biomarkers in larger patient cohorts are highly warranted.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Extramedullary disease; Immunotherapy; Multiple myeloma; Natural killer cells; SLAMF7